2020
DOI: 10.3390/joitmc6040147
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Optimizing the Structure of Teaching Techniques for Distance Learning in the Russian Higher Education System

Abstract: This study aims to develop a methodical approach to optimize the structure of teaching techniques and approaches to distance education, as exemplified by Russian universities, to enhance students’ professional competencies. A pedagogical experiment was conducted with the participation of 746 second to fourth year students majoring in engineering at the Ural Federal University in Russia. The coefficients for the relative importance of professional competencies were obtained through expert assessment. The number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…The aforementioned studies show that the syntax of the learning model adapted from other countries and the syntax of a learning model based on the local indigenous values of the Indonesian people has shown to have high effectiveness in improving learning quality (Gardanova et al, 2020). Meanwhile, Suastika and Sanjaya (2017) found that (1) the syntax of learning model is very easy to be applied by the teacher and easily to be understood by the students, because it is relevant to the sociocultural values that commonly grow and develop in the community; (2) the model steps require students to identify, seek information, analyse, infer and solve citizenship problems that are empirical, so as to develop students' critical thinking skills and (3) the applied learning model is able to develop spiritual skills, moral skills, social skills and intellectual skills at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned studies show that the syntax of the learning model adapted from other countries and the syntax of a learning model based on the local indigenous values of the Indonesian people has shown to have high effectiveness in improving learning quality (Gardanova et al, 2020). Meanwhile, Suastika and Sanjaya (2017) found that (1) the syntax of learning model is very easy to be applied by the teacher and easily to be understood by the students, because it is relevant to the sociocultural values that commonly grow and develop in the community; (2) the model steps require students to identify, seek information, analyse, infer and solve citizenship problems that are empirical, so as to develop students' critical thinking skills and (3) the applied learning model is able to develop spiritual skills, moral skills, social skills and intellectual skills at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…It was also noted that more and more students do not want and need traditional and flexible working hours. Thus, remote study became an ever more popular method, in order to obtain higher education which becomes clear by the number of the correspondence courses, which are offered at the university [3]. Distance learning has the potential to reach many more people through the use of online courses and other forms of learning such as social media and online learning.…”
Section: Introductionmentioning
confidence: 99%
“…Modern development of technical means of communication, the level of development of teaching competencies in the field of information technology, technical equipment of the overwhelming majority of Russian universities made it possible to pass this stage quite painlessly and practically without prejudice to the quality of education [3,4,5]. At the same time, the issue of developing feedback with participants in the educational process for timely informing the organizers about emerging situations and problems in order to eliminate them has received great urgency [6,7].…”
Section: Introductionmentioning
confidence: 99%